Determinants of Dividend Policy: Evidence from Indonesia's Islamic Capital Market - Laila Widya Hidayati; Sylva Alif Rusmita (Universitas Airlangga, 2024)
This study aims to determine the factors that can influence a company's decision in dividend policy for companies in the Jakarta Islamic Index 70 (JII70) during the 2018-2022 period. This research uses a quantitative method with Binary Logistic Regression analysis technique, assisted by the SPSS 21 program. The results show that the profitability variable has a significantly positive effect on the dividend policy decision. Dividend policy is also influenced by institutional ownership structure and company liquidity, which have a significantly negative effect on the company's decision to distribute dividends. However, investment opportunity and inflation do not affect the decision on dividend distribution policy. Thus, it can be said that the main determinant for companies in making decisions for dividend distribution policy to shareholders is influenced by the level of profitability, where the higher the profitability level, the higher the company's capability to distribute dividends. This research can serve as a consideration for investors in making investments with a certain return orientation, namely dividends.